Good Corporate Governance and Profitability: Evidence the Banking Sector in Indonesia - Fidriansyah, Septa; Andriana, Isni; Muthia, Fida (Jurnal Ilmu Manajemen, 2025)
The research aims to determine empirically the influence of Good Corporate Governance on banking profitability in Indonesia. The method used in the study is a quantitative method with secondary data sources obtained from good corporate governance reports and financial statements from each bank. The sample was obtained using purposive sampling, namely banks that had participated in CGPI in 2019-2023. This hypothesis was tested with multiple linear regression analysis techniques. Data collection techniques through documentation and data are processed through spss 26 software. The results of this study show that in banking, Good Corporate Governance as measured by managerial ownership, commissioners and internal audit has a positive and significant effect on profitability. Meanwhile, the board of directors and audit committee have a negative and significant effect on profitability.